Visually guided grasping produces fMRI activation in dorsal but not ventral stream brain areas - Culham, Jody C.; Danckert, Stacey L.; Souza, Joseph F. X. De; Gati, Joseph S.; Menon, Ravi S.; Goodale, Melvyn A. (Experimental brain research, 2003)
Although both reaching and grasping require transporting the hand to the object location, only grasping also requires processing of object shape, size and orientation to preshape the hand. Behavioural and neuropsychological evidence suggests that the object processing required for grasping relies on different neural substrates from those mediating object recognition. Specifically, whereas object recognition is believed to rely on structures in the ventral (occipitotemporal) stream, object grasping appears to rely on structures in the dorsal (occipitoparietal) stream. We used functional magnetic resonance imaging (fMRI) to determine whether grasping (compared to reaching) produced activation in dorsal areas, ventral areas, or both. We found greater activity for grasping than reaching in several regions, including anterior intraparietal (AIP) cortex. We also performed a standard object perception localizer (comparing intact vs. scrambled 2D object images) in the same subjects to identify the lateral occipital complex (LOC), a ventral stream area believed to play a critical role in object recognition. Although LOC was activated by the objects presented on both grasping and reaching trials, there was no greater activity for grasping compared to reaching. These results suggest that dorsal areas, including AIP, but not ventral areas such as LOC, play a fundamental role in computing object properties during grasping.